1999
DOI: 10.1063/1.479520
|View full text |Cite
|
Sign up to set email alerts
|

Quantum fluid dynamics in the Lagrangian representation and applications to photodissociation problems

Abstract: This paper considers the practical utility of quantum fluid dynamics ͑QFD͒ whereby the time-dependent Schrödinger's equation is transformed to observing the dynamics of an equivalent ''gas continuum.'' The density and velocity of this equivalent gas continuum are respectively the probability density and the gradient of the phase of the wave function. The numerical implementation of the QFD equations is carried out within the Lagrangian approach, which transforms the solution of Schrödinger's equation into foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 66 publications
0
66
0
2
Order By: Relevance
“…If done appropriately, such a decomposition can lead to very important ramifications for quantum trajectory methods (QTMs) 5,6,7,8,9,10,11,12,13,14 -i.e., trajectorybased numerical techniques for performing exact quantum dynamics calculations, based on Bohmian mechanics 15,16,17,18,19,20 -due to nonlinearity of the Bohmian equations of motion. In particular, the earlier series of articles has culminated in a set of trajectorybased time-dependent methods for computing stationary scattering quantities (the theoretical underpinning of all chemical reactions) in one degree of freedom (DOF).…”
Section: Introductionmentioning
confidence: 99%
“…If done appropriately, such a decomposition can lead to very important ramifications for quantum trajectory methods (QTMs) 5,6,7,8,9,10,11,12,13,14 -i.e., trajectorybased numerical techniques for performing exact quantum dynamics calculations, based on Bohmian mechanics 15,16,17,18,19,20 -due to nonlinearity of the Bohmian equations of motion. In particular, the earlier series of articles has culminated in a set of trajectorybased time-dependent methods for computing stationary scattering quantities (the theoretical underpinning of all chemical reactions) in one degree of freedom (DOF).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that the convergence of the least-squares procedure is greatly improved by using a logarithmic form of the density 15,17,19 ,…”
Section: Moving Least Squares Approximationmentioning
confidence: 99%
“…While there are a number of papers which have computed quantum trajectories having obtained the wave function, relatively little work has been done in developing computational methods based upon the description which does not rely upon first constructing the wave function. [10][11][12][13][14][15] However, Wyatt and co-workers have recently described a mesh-less finite-element method for integrating the de Broglie-Bohm equations using Lagrangian hydrodynamic trajectories. [16][17][18] Similar methods are widely used in computational fluid dynamics (CFD) to simulate fluid flow dynamics in porous media (such as an oil reservoir) and other systems with complex topologies.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, innova- * Electronic address: Email: Bill.Poirier@ttu.edu tions spearheaded by members of the chemical physics community have led to the use of quantum trajectory methods (QTMs) as a "synthetic" tool, i.e. to solve the time-dependent Schrödinger equation (TDSE) itself [10,11,12].…”
Section: Introductionmentioning
confidence: 99%